Effect of high-dose Ascorbic acid on vasopressor's requirement in septic shock - Mohadeseh Hosseini Zabet; Mostafa Mohammadi; Masoud Ramezani; Hossein Khalili (Wolters Kluwer Medknow Publications, 2016)
Objective: Effects of ascorbic acid on hemodynamic parameters of septic shock were evaluated in nonsurgical critically ill patients in limited previous studies. In this study, the effect of high-dose ascorbic acid on vasopressor drug requirement was evaluated in surgical critically ill patients with septic shock. Methods: Patients with septic shock who required a vasopressor drug to maintain mean arterial pressure >65 mmHg were assigned to receive either 25 mg/kg intravenous ascorbic acid every 6 h or matching placebo for 72 h. Vasopressor dose and duration were considered as the primary outcomes. Duration of Intensive Care Unit (ICU) stay and 28-day mortality has been defined as secondary outcomes. Findings: During the study period, 28 patients (14 in each group) completed the trial. Mean dose of norepinephrine during the study period (7.44 ± 3.65 vs. 13.79 ± 6.48 mcg/min, P = 0.004) and duration of norepinephrine administration (49.64 ± 25.67 vs. 71.57 ± 1.60 h, P = 0.007) were significantly lower in the ascorbic acid than the placebo group. No statistically significant difference was detected between the groups regarding the length of ICU stay. However, 28-day mortality was significantly lower in the ascorbic acid than the placebo group (14.28% vs. 64.28%, respectively; P = 0.009). Conclusion: High-dose ascorbic acid may be considered as an effective and safe adjuvant therapy in surgical critically ill patients with septic shock. The most effective dose of ascorbic acid and the best time for its administration should be determined in future studies.